First description of the karyotype of a eucharitid wasp (Hymenoptera, Chalcidoidea, Eucharitidae) - Santos, Igor Silva (Comp Cytogenet, 2015)
Abstract. The haploid karyotype of Kapala sp. (Eucharitidae), a parasite of the Neotropical ant Dinoponera lucida Emery, 1901 (Hymenoptera, Formicidae), is reported for the first time. It consists of four metacentric chromosomes. Chromosomes in the family Eucharitidae were unknown so far; therefore, our results confirm that multiple parallel chromosomal fusions have taken place in several lineages within the superfamily Chalcidoidea.